The Perspective of Community Health Center Workers toward Stunting Prevention Program during the COVID-19 Pandemic - Sukamto, Ika Sumiyarsi; Hartono, Hartono; Setyowati, Retno; Mulyani, Sri; Nintya, Dian; Sarah , Hanifah; Hanifah , Hasna Fatin; Maulina, Rufidah (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Since the COVID-19 outbreak occurred, the stunting prevention program in Indonesia has faced many challenges. Integrated Health Posts as the places where mothers can have their baby’s growth measured were closed and restricted. AIM: The purpose of this study is to describe stunting prevention program during the COVID-19 pandemic from the perspective of the Community Health Center workers. METHODS: This research used the qualitative research method. Its primary and secondary data were collected through semi-structured open-ended questionnaire and in-depth interviews with 20 Community Health Center workers and officials of the Health Office of Surakarta City. This study was conducted on April 12, 2021 at Universitas Sebelas Maret, Indonesia. The data of the research were manually analyzed to categorize the thematic analysis based on its objectives. Purposive sampling was used determine the participants for its in-depth interviews. They consisted of 20 health care workers. RESULTS: During the pandemic, the implementation of stunting prevention activities was hampered due to the government’s focus on the COVID-19 prevention program, the lack of commitment and participation of social workers, the invalid measurement from social workers, the social restrictions, and the fear of community gathering. The health cadres reported the findings using text messages rather than book measurements to follow the social restriction regulation. Some also did home visits to measure the toddlers’ growth. A commitment to tackle stunting and a workflow is therefore in demand so that stunting-related activities are not affected by the pandemic. CONCLUSION: Obstacles in the stunting prevention program during the pandemic were felt by cadres, health centers, and mothers of toddlers where they could not do the regular weighing. Thus, coordination and collaboration of various sectors are required to handle the stunting management.